Compounds from the imidazole group as copper corrosion inhibitor in acidic sodium sulphate solution - Ana Simonović; Milan Radovanović; Mihajlović Marija Petrović; Milan Antonijević (Zaštita Materijala)
To estimate influence of 2-mercapto-1-methylimidazole and 4(5)methil-imidazole on electrochemical behaviour of copper electrode in 0.5 moldm-3 Na2SO4 solution, pH 3, following methods were used: open circuit potential measurements, potentiodynamic polarization, chronoamperometry. Potentiodynamic measurements showed that investigated inhibitors can be used as copper corrosion inhibitor in acidic 0.5 moldm-3Na2SO4 solution. Increase of concentrations leads to better inhibitor efficiency. These results were confirmed using the chronoamperometry. Adsorption of 2-mercapto-1-methylimidazole and 4(5)methil-imidazole obeys Langmuir adsorption isotherm.